Tropical Architecture Application Study on the Facade of Aceh Tamiang Regency Government Offices - Dafrina, Armelia; Syahputra, Agung (Rumoh Journal of Architecture, 2024)
Indonesia has a tropical climate characterized by high rainfall, warm temperatures, high humidity, and relatively low wind speeds. Building design must be adapted to these climate conditions to achieve efficiency and comfort, as well as to reduce the use of air conditioning systems. This study focuses on four government office buildings in Aceh Tamiang Regency: the Regent’s Office, DPRK (Regional People’s Representative Council), BPKD (Regional Financial and Asset Management Agency), and the Ministry of Religious Affairs Office. The research method used is qualitative descriptive, with data obtained through observation, interviews, literature review, and documentation. This study aims to examine the extent to which tropical architectural principles are applied to these buildings, including building orientation, use of natural ventilation, pitched roofs, natural lighting, local materials, and other design elements. The results show that all four buildings incorporate various aspects of tropical architecture, such as optimal building orientation for air circulation, the use of local materials, and roof designs suitable for a tropical climate. This research is expected to provide new insights into the application of tropical architecture and serve as a reference for building planning in other tropical climate regions.